2024
DOI: 10.1520/jte20230417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Influencing Factors Associated with a New Tunnel Waterproofing for Improved Impermeability

Bingxiang Yuan,
Jingkang Liang,
Hengzheng Lin
et al.

Abstract: Leakage associated with deformation joints seriously affects tunnel structures. Existing tunnel deformation joint waterproofing structures have high construction costs and inconvenient maintenance requirements. This work proposes a new tunnel deformation joint waterproofing structure. Specifically, this structure combines Ω type water stop, an externally attached water stop, and a concrete component. An impermeability test compares standard waterproofed specimens to improved specimens. Under a variety of defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…where W ex−3−1 -the external power of the triangle bulk C a,0 C a,1 O a,0 , and S C a,0 C a,1 O a,0 is the size of the triangular bulk C a,0 C a,1 O a,0 . The expression W ex−3−2 of the external power of the triangle mass C a,0 C a, f C a, f +1 at its self-weight is presented by expression (36).…”
Section: Power Of External Workmentioning
confidence: 99%
See 2 more Smart Citations
“…where W ex−3−1 -the external power of the triangle bulk C a,0 C a,1 O a,0 , and S C a,0 C a,1 O a,0 is the size of the triangular bulk C a,0 C a,1 O a,0 . The expression W ex−3−2 of the external power of the triangle mass C a,0 C a, f C a, f +1 at its self-weight is presented by expression (36).…”
Section: Power Of External Workmentioning
confidence: 99%
“…The tunnel in the karst zone is constructed with the shield method, and this segment of the interval tunnel mainly goes across the moderately weathered dolomite formation. The size of the cavity space [36] in this subway interval section ranged from As shown in Figure 4d, when the clearance from the tunnel to the cavity is 3 m, and the cohesion within the geotechnical body is 800 kPa, the safety factor obtained by using the analytical solution method of calculating the probability of failure as well as the reliability index of this deeply buried karst tunnel is 16.12% smaller than the value obtained using the strength reduction theory with finite element. When the clearance from the tunnel to the cavity is 8 m, and the cohesion within the geotechnical body is 800 kPa, the safety factor obtained by using the analytical solution method of calculating the probability of failure as well as the reliability index of this deeply buried karst tunnel is 27.13% smaller than the value obtained using the strength reduction theory with finite element.…”
Section: Information On the Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…By evaluating the possibility of using existing numerical models of mortar and concrete machinery on wood-based cementitious composites, Ndong Engone et al [16] identified the parameters that have to be adjusted in the models. In foreign countries, some new technologies have emerged, such as adding modifiers to enhance solidification effects and utilizing detection systems for construction monitoring [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, reducing the cement percentage minimizes the compressive strength of lightweight soil when different EPS contents are used. Yuan et al [29] conducted a study to examine the variables that impact the efficiency of a new technique for waterproofing tunnels in order to make athem more impermeable. The results of the tests demonstrated a clear connection between the difference in displacement and the number of times the materials were subjected to fatigue loading, which directly affects the amount of seepage.…”
Section: Introductionmentioning
confidence: 99%